Evaluation of the influence of thiotriazoline on the cytokine status disturbances in the blood serum under the condition of experimental contact dermatitis and experimental pneumonia - M. M. Regeda-Furdychko (Kazimierz Wielki University, 2020)
The aim of our research was to determine the character of the disturbances content level of pro-inflammatory interleukin-6, tumor necrosis factor-α and anti-inflammatory cytokine interleukin-10 (IL-10) in the serum of guinea pigs and estimation of  thiotriazoline influence on the cytokine profile in the conditions of formation of  combined pathology - experimental contact dermatitis and experimental pneumonia. It has been determined significant advantage of pro-inflammatory cytokine activity, which increasing according the development of the combined pathological process and, simultaneously, reducing the anti-inflammatory IL-10. It has been detected corrective action of  thiotriazoline on the investigated indices of cytokine profile.